pengaruh Pengaruh Kemampuan Numerik dan Kemampuan Spasial Terhadap Kemampuan Menyelesaikan Soal Matematika Siswa Kelas IX SMP Negeri 4 Gerung Tahun Ajaran 2024/2025 - Sartika, Luwy; Nurul Hikmah; Ulfa Lu’luilmaknun; Syahrul Azmi (Mandalika Mathematics and Educations Journal, 2025)
This research is motivated by students’ difficulties in solving mathematical problems, which are caused by their low numerical and spatial abilities. These difficulties are caused by the low numerical and spatial abilities. Numerical ability is related to understanding and performing basic arithmetic operations, while spatial ability involves understanding relationship, visualization, and spatial orientation. Therefore, the aim of this study is to determine the influence of numerical and spatial abilities on the mathematical problem solving skills of IX grade students at SMP Negeri 4 Gerung in the 2024/2025 academic year. This research is a quantitative study using the ex post facto method. The population consists of all IX grade students, totaling 173, with a purposive sampling technique used to select 36 students as the sample. Data collection was conducted through numerical ability test, spatial ability test, and mathematics problem solving test. D ata analysis techniques included descriptive statistical analysis and inferential statistical analysis. The results of the study indicate a significant influences of numerical and spatial abilities on mathematical problem solving skill. Simultaneously, these two variables contributed 64,7% to students’ problem solving abilities. Thus, improving numerical and spatial abilities can be an effective strategy for enhancing students’ mathematical problem solving skills.